(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
At present, there are several dispute resolution mechanisms that are available to resolve disputes between states. International law regards all states to be standing at an equal footing that makes state consent to be required in the dispute resolution process. Meanwhile, Islamic law presents dispute resolution as one tenet to achieve justice which is in line with the Shariah and the Prophet Muhammad (pbuh) traditions. This article will describe and analyse the dispute resolution mechanisms in international law and Islamic law by focusing on the distinctive traits between these two. This is needed in order to evaluate suggestions on how to ensure the establishment of the International Islamic Court of Justice (IICJ) as a convenient forum for dispute resolution among Muslim States that was proposed by the Organization of Islamic Cooperation (OIC) in 1981 but has not been materialised until today. Using qualitative method and library-based research, primary and secondary sources from various sources are examined to provide a comparative analysis on the concept of dispute resolution in international law and Islamic law. The preliminary findings from this study suggest that in order to properly established the IICJ as a medium of settling the difference of views among the Muslim states, it must be encouraged that all Muslim states must ratify the Court’s Statute. The OIC must organise inclusive dialogues to explain the working of the Court particularly to its member states to make it workable in resolving disputes and achieve considerable results in preserving peace as well as securing justice between Muslim states.